Endolithic Algae Affect Modern Coral Carbonate Morphology and Chemistry - Krause, Stefan; Liebetrau, Volker; Nehrke, Gernot; Damm, Timo; Büsse, Sebastian; Leipe, Thomas; Vogts, Angela; Gorb, Stanislav N.; Eisenhauer, Anton (Frontiers in Earth Science, 2019)
While burial diagenetic processes of tropical corals are well investigated, current knowledge about factors initiating early diagenesis remains fragmentary. In the present study we focus on recent Porites microatolls, growing in the intertidal zone. This growth form represents a model organism for elevated sea surface temperatures and provides important but rare archives for changes close to the seawater/atmosphere-interface with exceptional precision on sea level reconstruction. As other coral growth forms, microatolls are prone to the colonization by endolithic green algae. In this case the algae can facilitate earliest diagenetic alteration of the coral skeleton. Algae metabolic activity not only results in secondary coral porosity due to boring activities, but may also initiate reprecipitation of secondary aragonite within coral pore space, a process not exclusively restricted to microatoll settings. In the samples of this initial study, we quantified a mass transfer from primary to secondary aragonite of around 4% within endolithic green algae bands. Using δ18O, δ13C, Sr/Ca, U/Ca, Mg/Ca, and Li/Mg systematics suggest that the secondary aragonite precipitation followed abiotic precipitation principles. According to their individual distribution coefficients the different isotope and element ratios showed variable sensitivity to the presence of secondary aragonite in bulk samples, with implications for microatoll-based sea surface temperature (SST) reconstructions. The secondary precipitates formed on an organic template, presumably originating from endolithic green algae activity. Based on laboratory experiments with the green algae Ostreobium quekettii we propose a conceptual model that secondary aragonite formation is potentially accelerated by an active intracellular calcium transport through the algal thallus from the location of dissolution into coral pore spaces. The combined high-resolution imaging and geochemical approach applied in this study shows that endolithic algae can possibly act as a main driver for earliest diagenesis of coral aragonite starting already during a coral’s life span.